Thirty Year Old Female Presented with Nipple Destruction: A Case Report - Rahman, Md Mustafizur; Ahmed, Nadim; Ahmad, Sami; Alam, Shoaeb Imtiaz; Hassan, Mohammad Rashedul; Islam, Mansurul; Hasan, ASM Farhad Ul (Journal of Shaheed Suhrawardy Medical College, 2019)
Paget’s disease of the breast is a rare type of cancer of the nipple–areola complex and that is often associated with an underlying in situ or invasive carcinoma. It is often misdiagnosed as eczema of breast and treatment is delayed. Here we present a case where a 30 year old female presented with itching ulceration and destruction of her left nipple. She was treated initially by local physicians by applying local ointments but as her condition did not improve she was admitted to department of surgery Shaheed Suhrawardy Medical College hospital where she was diagnosed as Paget’s disease with infiltrating ductal cell carcinoma. She underwent modified radical mastectomy with axillary clearance and referred to oncology department for further management. J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 81-83